Pronunciation Errors of English Front Vowels by Yemeni EFL Learners - Ali Mohammed Saleh Al-Hamzi; Abdul hakim Ahmed Sallam Al-Shrgabi; Ali Saleh Ahmed Al-Haidari; Mansour Mohamed Ali Faraj; Taha Ahmed Ali Al-Housali (PAROLE: Journal of Linguistics and Education, 2021)
In the domain of English as a foreign language, many learners still face some difficulties in articulating vowel sounds of English, particularly the front ones. This study attempts to describe Yemeni EFL learners' errors while pronouncing the English front vowels. The subject of this study was the eighth-semester students studying at the English department, Faculty of Education, Mahweet branch, Sana'a University. The descriptive qualitative approach was utilized in this study. The data was collected by recording learners' pronunciation of English front vowel minimal pairs. The data was then compared with the ones produced by an English native speaker. The findings resulted were confirmed by the spectrogram technique to identify the formants of F1 and F2 made by the learners in Praat Software Device. English front vowels /i / - / I /- / Ԑ / and / ae / were the target sounds. The study's findings revealed that Yemeni EFL learners' pronunciation differs from those produced by native English speakers. It was also revealed that Yemeni EFL learners are still struggling in articulating English front vowel sounds due to the influence of the sound system of their native language that causes such pronunciation problems in the target language.